Design and testing of a novel human-powered generator device as a backup solution to power Cranfield´s Nano-Membrane Toilet - Perez Lopez, Eloy (Cranfield University, 2014)
In today’s world there are 2.6 billion people that lack basic sanitation (37% of world inhabitants). In August of 2012, Cranfield University was awarded by the Bill & Melinda Gates Foundation with $810,000 to produce a prototype of the Cranfield’s innovative Nano-membrane Toilet (NMT). Finally, the prototype is going to be exhibited at the “Reinvent the Toilet Fair” during 21st and 22nd of March 2014 in the Taj Palace Hotel, New Delhi (India). Cranfield’s NMT demands electricity for its daily performance. Nevertheless, it is targeted to off-grid communities. Consequently, a human-powered generator (HPG) was selected as a backup solution. The current MSc by Research aimed to design and test of a prototype of the aforesaid HPG. Moreover, to promote its usage, a portable power supply unit is designed to store energy and power small-loads like charging mobile phones and electric lighting. To select the most suitable design for our case study, a methodology using the Technique for Order of Preference by Similarity to the Ideal Solution has been developed. As a result the plugged-in bike HPG alternative was selected. Next, prototypes of this generator and the portable power supply unit were developed, tested and shipped for display. While testing of the plugged-in generator and portable power supply unit, 26 Watt-hours (Wh) were harvested over 15 minutes, with its corresponding average charging power of 105 Watts. Nevertheless, the present study concludes 96 Wh as a more accurate energy level to be harvested during one hour of pedalling. Considering 96 Wh of energy, a round-trip battery efficiency of 70% (lead-acid), and a NMT’s demand of 283 Wh; a 10 people household needs to pedal the HPG over 4 hours and 20 minutes. Nevertheless, if considering an 85% inverter efficiency, 57.12 Wh are available to fully charge one mobile phone (5.6 Wh) and provide 4.5 hours of room and desk lighting (11 Watts bulb).
Keywords: Human development; human power; TOPSIS Method; Multi-criteria Decision Method